Trend Analysis of Land Cover Changes, Population and Settlement Distribution to Land use Assessment in Kebumen Regency - Putri, Ratih Fitria; Budiman, Lucia Sandra; Fauziyanti, Navila Ulfi; Adalya, Natasya Michelle (Universitas Negeri Semarang, 2019)
The condition of population growth in Kebumen Regency tends to increase every year. This dynamic population condition can also change the land cover trends. Based on this background, identification of trends in land cover changes is quite interesting to study which aims to facilitate land use planning for stakeholders in the relevant region. The objectives of the study include (1) analyzing the dynamics of the population of Kebumen Regency, (2) analyzing the pattern of land cover changes, and (3) analyzing the population pressure on agricultural land. This study used aerial photography data from 2006 to 2016 to determine land cover types and the GIS conditional functions were used for settlement distribution mapping. The data processing results was done by quantitative descriptive analysis. The results showed that (1) Kebumen Subdistrict is an area with the highest population among other sub-districts and it has high population pressure towards land uses around 2,478 people/Km2, (2) mixed gardens each year tend to decrease in area of 98.39 km2, while settlements and paddy fields increase by 43.55 km2 and 235.95 km2. (3) Increase in population numbers and density in some districts of Kebumen are directly proportional to the level of pressure on agricultural land which is also high.